2023
DOI: 10.1186/s42358-023-00294-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the synovial levels of RANKL and OPG in rheumatoid arthritis, spondyloarthritis and osteoarthritis

Abstract: Introduction In chronic arthropathies, there are several mechanisms of joint destruction. In recent years, studies have reported the implication of receptor activator of nuclear factor kappa-B ligand (RANKL) and osteoprotegerin (OPG) in the process of activation and differentiation of osteoclasts, a key cell in the development of bone erosion. The RANKL/OPG ratio is increased in the serum of patients with malignant diseases and lytic bone disease, as well as rheumatoid arthritis (RA). The objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…OPG/RANKL is assumed to be critical in bone metabolism-regulating mechanism that affects osteoclastogenesis. OPG inhibits bone resorption by blocking RANKL from attaching to its receptors, while RANKL promotes bone resorption via interacting with its receptors expressed on osteoclasts [73,74]. The current investigation found that curcumin co-encapsulation with meloxicam (nCur/Mlx) significantly (p ≤ 0.05) up-regulated the mRNA expression of OPG and down-regulated RANKL expression in adjuvantinduced arthritic rats, as compared to monotherapy (Figure 6G,H).…”
Section: Discussionmentioning
confidence: 54%
“…OPG/RANKL is assumed to be critical in bone metabolism-regulating mechanism that affects osteoclastogenesis. OPG inhibits bone resorption by blocking RANKL from attaching to its receptors, while RANKL promotes bone resorption via interacting with its receptors expressed on osteoclasts [73,74]. The current investigation found that curcumin co-encapsulation with meloxicam (nCur/Mlx) significantly (p ≤ 0.05) up-regulated the mRNA expression of OPG and down-regulated RANKL expression in adjuvantinduced arthritic rats, as compared to monotherapy (Figure 6G,H).…”
Section: Discussionmentioning
confidence: 54%